Civil liberties & Canadian federalism. - Scott, F. R. (Francis Reginald), 1899-1985 (Alan B. Plaunt memorial lectures, 1959)
Professor Scott discusses the relationship between civil liberties and the Canadian constitution in the light of the steps now being taken to write a Bill of Rights into the law. But he takes a much wider point of view than that suggested by present political alternatives.